Characteristics of the attack from under-18 to under-22 players in men`s and women`s beach volleyball categories - Gomis-Gomis, M. J.; Perez-Turpin, J. A.; Elvira-Aranda, C.; Campos-Gutierrez, L. M.; Perez-Suarez, P. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In beach volleyball, attacks can be subcategorized into spikes and shots. By definition, the spikes are executed with maximum power and the ball trajectory after hand contact follows a straight line. On the other hand, the shots are relatively softly attacked balls, which are used to place the ball into unprotected areas of the curt. Currently, there is hardly any information in literature related to the way of the execution of the attack in relation to gender and age group. Therefore, the purpose of this study is to determine types of attack used in categories from under-18 to under-22 according to gender in order to have a deeper knowledge about the game in the lower categories of beach volleyball. Methods: A total of 1.518 attacks from men`s games (33 sets) and 1.504 attacks from women`s games (36 sets) were analysed. The sample included 40 teams from under-18 to under-22 that qualified for the semi-finals and finals of the 2016 World Championships and the 2016 European Championships. An observational, descriptive, and correlational design was used, together with a notational analysis in order to assess the different features of the attack execution. The free software used to analyse the videos was LongoMatch 1.0. The variables studied were: type of attack, efficacy, area and place of attack, gender and age group. Results: The results show that for both genders: women clearly favour shots (56%) over spikes (44%) as long as men lightly favour spikes (52%) over shots (48%). Moreover, while cross-court spikes are the popular in men (35%). women play about 30% cross-court spikes as well as line shots. There was a similar attacking quality in both genders: 51% positive. 34% neutral and 15% negative. In both genders, there is a clear tendency to attack by zone 2 (58%). And finally, the areas of attack most used were Z5 and Z1 (the corners), least used were Z3 and Z6 (the middle). Conclusion: The present study shows that women and men use differently the types of attacks, although the placements, effectiveness and areas of attack are quite similar in both genders. Coinciding with Koch et. al. (2009) and Medeiros et. al. (2014) men use more spikes than women, and the use of the spike in the lower categories is fewer than in the senior category. According to Mesquita et. al. (2004). spike is more effective than shot in men. In conclusion, the results of the study provide coaches and researchers new information about performance indicators of the attack.